Registration procedures, measurement and quantification of electrodermal activity - Román, Francisco; Gómez-Amor, Jesús; Martínez-Selva, José M. (Anales de Psicología / Annals of Psychology)
In this paper the methodology in the study of electrodermal activity is reviewed. Types and methods of recording electrodermal activity, types of electrodes and electrolyte gel in the register of skin conductance, types of measuring skin conductance, schemes of basic circuits used in analysing resistance measurements and skin conductance, and systems for detection and measurement of the response of skin conductance